2020
DOI: 10.1155/2020/7650104
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Risk Factors for Renal Impairment among HIV-Infected Patients Treated with Tenofovir Disoproxil Fumarate-Based Antiretroviral Regimen in Southern Vietnam

Abstract: Background. The situation of renal impairment among HIV-infected patients treated with TDF-based antiretroviral (ARV) regimen greater than 3 years is little known when TDF use has been promptly increasing in Vietnam. Methods. We analyse demographic and clinical data from a cross-sectional survey of 400 HIV-infected patients aged ≥18 years, who were treatment-naive or switched TDF regimen within over 3 years between November 2018 and March 2019. Serological tests for serum creatinine, ALT, and AST were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
3
2
Order By: Relevance
“…The CKD prevalence (4.53%) of the current study is in line with the findings of a study in Tikur Anbessa Specialized Hospital (TASH), 4.8%. 10 However, the finding was lower than the results of studies done in Asia, 9.86%, 8 Vietnam, 8.5%, 12 US Veterans, 14.3%, 11 and University of Gondar Teaching Hospital. 13 On the other hand, the result of the current study was higher than the finding of a study in Cape Town, South Africa, 2%.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…The CKD prevalence (4.53%) of the current study is in line with the findings of a study in Tikur Anbessa Specialized Hospital (TASH), 4.8%. 10 However, the finding was lower than the results of studies done in Asia, 9.86%, 8 Vietnam, 8.5%, 12 US Veterans, 14.3%, 11 and University of Gondar Teaching Hospital. 13 On the other hand, the result of the current study was higher than the finding of a study in Cape Town, South Africa, 2%.…”
Section: Discussioncontrasting
confidence: 59%
“…Literatures revealed that older age, 7 , 8 , 12 , 13 female sex, 7 low BMI, 12 , 13 and low CD4 count 13 were significantly associated with CKD. In contrast, the present study showed no significant association of female sex, low BMI, and low CD4 count with CKD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hoang et al reported that 8.5% out of 400 cases under tenofovir therapy had renal dysfunction that was related to older age, lower BMI and no exposure to isoniazid therapy (16). Anthropometric and demographic variables and tuberculosis treatment in our study were not related to renal function.…”
Section: Discussioncontrasting
confidence: 56%